Comparison of single versus dual antiplatelet therapy after TAVR: A systematic review and meta‐analysis. Issue 4 (8th March 2018) - Raheja, Hitesh; Garg, Aakash; Goel, Sunny; Banerjee, Kinjal; Hollander, Gerald; Shani, Jacob; Mick, Stephanie; White, Jonathan; Krishnaswamy, Amar; Kapadia, Samir
Abstract: Objective: We aim to evaluate the efficacy of dual versus single anti‐platelet therapy (SAPT) after TAVR through a systematic review and meta‐analysis of published research. Background: Dual antiplatelet therapy (DAPT) with aspirin and clopidogrel is a commonly practiced strategy after transcatheter aortic valve replacement (TAVR). However, there is lack of sufficient evidence supporting this approach. Method: We searched PubMed, EMBASE, the Cochrane Central Register of Controlled trials, and the clinical trial registry maintained at clinicaltrials.gov for randomized control trials (RCT) and observational studies comparing DAPT with SAPT post TAVR. Event rates were compared using a forest plot of relative risk with 95% confidence intervals using a random‐effects model assuming inter‐study heterogeneity. Results: A total of six studies (3 RCTs and 3 observational studies, n  = 840) were included in the final analysis. Compared to SAPT, DAPT was associated with increased risk of significant bleeding (life threatening and major) [RR = 2.52 (95% CI 1.62–3.92, P  < 0.0001)] with the number needed to harm for major or life‐threatening bleeding calculated to be 10.4. There was no significant difference in the incidence of stroke [RR = 1.06 (95% CI, 0.43–2.60, P  = 0.90)], spontaneous myocardial infarction [RR = 2.08 (95% CI, 0.56–7.70, P  = 0.27)] and all‐cause mortality [RR = 1.18 (95% CI, 0.68–2.05, P  = 0.56] in the DAPT and SAPT groups. Conclusion: In this small meta‐analysis of DAPT versus SAPT after TAVR, DAPT did not prevent stroke, myocardial infarction or death while the risk of bleeding was higher. Results from ongoing trials are awaited to determine the best anti‐thrombotic approach after TAVR.